(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Aim: The aim of this research is to investigate the efficacy of ultrasonography as a diagnostic tool for determining the presence of carpal tunnel syndrome (CTS) in either the left or right upper limb of participants who have a suspicion that they may have the condition. Method: This research was conducted over the course of a year at the Mayo Hospital's radiology and neurology sections in Lahore. The research was cross-sectional in nature. The remaining 128 individuals were comprised of healthy volunteers (n=64) and patients (n=64), respectively. An examination of the nerve conduction was carried out on each and every patient (NCS). Initially, the diagnostic technique included measuring the median nerve's cross-sectional area near the carpal tunnel's opening. The results from the NCS and the ultrasound were then compared and contrasted. NCS testing in conjunction with a traditional medical evaluation was regarded as the gold standard. Results: The electro-diagnostic examinations correlated positively with the median nerve's cross-sectional area (r = 0.618, p = 0.001). This resulted in a Pearson correlation of 0.3913 between the two variables. A condition ranging from moderate to severe was present in over two-thirds of individuals who were diagnosed. In a similar vein, sixty percent of them had a cross-sectional area that was more than 0.15 cm2. A paired t-test revealed that there was a substantial difference in the perimeters (p = 0.0001, confidence interval = 95%). This difference was shown to exist between the two groups. The following results were obtained with a cut-off CSA of > 0.09 cm2: sensitivity of 54 out of 64, specificity of 90 out of 64, positive predictive value of 54 out of 60, and negative predictive value of 58 out of 68. Conclusions: If the median nerve's cross-sectional area is more than 0.09 cm2, a diagnosis of carpal tunnel syndrome may be established. When a patient is suspected of having carpal tunnel syndrome, an ultrasound may prove to be a helpful new diagnostic technique for evaluating the median nerve. Diagnostic methods that may be helpful in determining whether or not a patient has Carpal Tunnel Syndrome include electrodiagnostic testing, nerve conduction studies, electromyography, and high-resolution ultrasonography.